ANALYSIS OF THE IMPLEMENTATION OF DOMESTIC VIOLENCE PREVENTION IN INDONESIA - Ani Agus Puspawati; Bambang Utoyo; Yudha Suchmasasi (Universitas Padjadjaran, 2023)
The goal of the 2004 Law Number 23 on the Elimination of Domestic Violence is to end domestic violence in all of its manifestations. Cases of domestic abuse surged eightfold or by 792 per cent. The purpose of this research is to examine how domestic abuse prevention initiatives are being carried out in Indonesia. A qualitative descriptive literature review is the methodology used. This research shows that community outreach and education are two ways that prevention may be implemented, including a variety of stakeholders. Policy goals may be supported by providing chances for non-implementing agency actors to engage in policy implementation. In order to sustain stakeholder commitment, enhance the ability of implementing officers to undertake education, lessen sectoral ego, and promote stakeholders' comprehension of policy aims, coordination between stakeholders must enhance integrated collaboration and communication. The availability of human resources is one of the elements that impact a policy or program's implementation and success. Incompetent or underqualified policy implementers may be the cause of a policy's lacklustre execution. The reason that the community does not always recognize the Law on the Elimination of Domestic Violence is partly due to the variety of cultural values and social behaviours. It becomes more difficult to create strict and unambiguous standards the more diverse the services offered, the more diverse the conduct that is governed. As a result, it is advised to optimize preventative initiatives by fortifying family dynamics, improving cooperation with non-governmental organizations in the field of education, and putting digital anti-violence campaigns into action. The effectiveness of policy implementation depends on all policy implementers including the prevention of domestic violence into their work.